2018
DOI: 10.1186/s12944-018-0893-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic activity of Dracocephalum kotschyi involves FOXO1 mediated modulation of PPARγ expression in adipocytes

Abstract: BackgroundDracocephalum kotschyi, as a wild-growing flowering plant (from Lamiaceae family), is locally prescribed for its various health-promoting properties including hypolipidemic and hypoglycemic effects. To evaluate the scientific basis of the traditional use of Dracocephalum kotschyi extract (DKE), we aimed to disclose its mode of action with main focus on white adipose tissue of diabetic rats.MethodsStreptozotocin-induced diabetic rats were exposed to different doses of DKE for 28 days followed by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The Prunus mume seed extract can increase the level of collagen and the SIRT1 mRNA expression and decreases the metalloproteinase 1 mRNA expression on mouse back dorsal skin tissue 5 . The extract from Dracocephalum kotschyi significantly up-regulates p-AKT, p-FOXO1, PPAR, and SREBP-1 expressions in adipose tissue 45 . The extracts of Retama monosperma (L.) Boiss.…”
Section: Discussionmentioning
confidence: 93%
“…The Prunus mume seed extract can increase the level of collagen and the SIRT1 mRNA expression and decreases the metalloproteinase 1 mRNA expression on mouse back dorsal skin tissue 5 . The extract from Dracocephalum kotschyi significantly up-regulates p-AKT, p-FOXO1, PPAR, and SREBP-1 expressions in adipose tissue 45 . The extracts of Retama monosperma (L.) Boiss.…”
Section: Discussionmentioning
confidence: 93%
“…The Prunus mume seed extract can increase the level of collagen and the SIRT1 mRNA expression and decreases the metalloproteinase 1 mRNA expression on mouse back dorsal skin tissue 5 . The extract from Dracocephalum kotschyi signi cantly up-regulates p-AKT, p-FOXO1, PPAR, and SREBP-1 expressions in adipose tissue 42 . The extracts of Retama monosperma (L.) Boiss.…”
Section: Discussionmentioning
confidence: 97%
“…There are several reports about the useful effects of some Drcacephalum plants in improving hyperglycemia and hyperlipidemia ( 31 32 33 ). D. kotschyi is a well-known species in this genus with various therapeutic properties including blood lipid-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…Aslian et al . reported that D. kotschyi extract decreased blood levels of triglycerides (54%), total cholesterol (40%), LDL (54%), and blood glucose (25%) and increased HDL (45%) in adipose tissues in diabetic rats ( 32 ). In their in vitro study, D. kotschyi extract augmented expression of some crucial genes involved in lipid metabolism and adipogenesis including peroxisome proliferator-activated receptor gamma (PPARγ), sterol regulatory element-binding type 1 (SREBP-1), forkhead box O-1 (FOXO1), and protein kinase B while suppressed c-Jun N-terminal kinase (JNK) in 3T3-L1 adipocyte cells ( 32 ).…”
Section: Discussionmentioning
confidence: 99%